Temperature and soil water potential in dry bean sole cropping and maize-bean intercropping during the dry season - Portes, Tomás de Aquino; Guimarães, Cleber Morais; Aidar, Homero (Pesquisa Agropecuaria Brasileira, 2014)
This experiment was conducted to clarify why beans in intercropping frequently yield better than in sole cropping. The parameters under investigation were soil temperature and water potential at 10 cm and 20 cm depth, air temperature at 5 cm above the soil surface (under the bean canopy), and the profile of solar radiation within the maize canopy. The results showed that after a period of drought, soil moisture under the maize stand was higher than that in bean sole cropping. Air temperature as well as the soil temperature at 10 cm and 20 cm depth were lower in intercropping than in the bean sole cropping system. The higher soil moisture and lower air and soil temperatures in intercropping were attributed to lower incidence of solar radiation at ground level and to the wind barrier formed by maize plants.